Efektifitas Edukasi Video AI (Artificial Intelligence) Terhadap Pengetahuan Dalam Kepatuhan Minum Obat Hipertensi - Cindy Novitasari Rahayu; Mizam Ari Kurniyanti; Ahmad Guntur Alfianto (Universitas Pahlawan Tuanku Tambusai, 2025)
Compliance with taking medication can influence the level of knowledge of elderly people and can be increased through providing health education using educational video media. The aim of this research is to analyze the effectiveness of AI videos on knowledge in adherence to taking medication in elderly people with hypertension. This research used a quantitative method with a pre-experimental design and a one group pre-post test approach carried out on 30 hypertensive elderly respondents who were selected using a purposive sampling technique. The results of the study showed that the dominant age data was >80 years as many as 17 people ((56.7%) with female gender as many as 17 people (56.7%) and the majority of occupations were farmers, the average result given the intervention was 3.06 and the results after intervention was 5.46 and after carrying out the T-test, the P value was 0.000 (<0.05), which means that it was concluded that there was significant effectiveness of AI educational videos on the level of knowledge in medication adherence.